Thermal behavior of concentrated oil-in-water emulsions based on soybean oil and palm kernel olein blends - Ibrahim, Nor Hayati; Che Man, Yaakob; Tan, Chin Ping; Nor Aini, Idris (Elsevier, 2009)
Droplet size distribution and thermal behavior of concentrated oil-in-water emulsions based on soybean oil (SBO)/palm kernel olein (PKO) blends were investigated. The emulsions were prepared using 70% (wt./wt.) oil blends of SBO/PKO as dispersed phases and stabilized by egg yolk. An increase in PKO level (0–40% wt./wt.) in the oil dispersed phase volume fraction caused significant increases (p < 0.05) in volume-weighted mean diameter (d4,3). The DSC data suggested that crystallization of the emulsions was induced by a ‘template effect’ of yolk constituents via a surface heterogeneous nucleation. Emulsions with 0–20% (wt./wt.) PKO levels in the dispersed phase demonstrated a good cool–heat stability even after three successive thermal cycles (from 50 °C to −70 °C at 10 min/°C). After the first thermal cycle, emulsions with 30% and 40% PKO levels in the oil dispersed phase were destabilized due to strong coalescence and crystallized via volume-surface heterogeneous nucleation. The unstable emulsions were attributable to high level of saturated triacylglycerols from PKO, with high droplet size characteristic, causing them to be more prone to partial coalescence.